Progressive multifocal leukoencephalopathy in the clinical practice of a neurologist. Case report - Yuliana A. Belova; Sergey V. Kotov (ZAO "Consilium Medicum", 2024)
Progressive multifocal leukoencephalopathy (PML) is an opportunistic infection with severe brain damage caused by the JC-virus, against the background of immunosuppressive conditions. The diagnosis of PML is complex and includes: the clinical picture, neuroimaging data, the presence of JC-virus DNA in samples of cerebrospinal fluid or brain tissue. HIV-associated PML is difficult to diagnose. In patients with multiple sclerosis, an increase in the incidence of PML is associated with the use of natalizumab. Increasing alertness towards the development and detection of PML makes it possible to achieve a favorable outcome.